2021
DOI: 10.3390/ani11092605
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Combinations of Dietary Vitamin A, Protein Levels, and Monensin on Inflammatory Markers and Metabolites, Retinol-Binding Protein, and Retinoid Status in Periparturient Dairy Cows

Abstract: The objective of this study was to determine the effect of feeding different combinations of dietary vitamin A supplementation (0 or 110 IU/kg body weight), protein (10.3% or 12.2%), and an ionophore (monensin at 0 or 400 mg/day) on retinoid metabolism and immune function of dairy cows. Eighty multiparous Holstein dairy cows were studied from d −35 to +21 relative to expected parturition in a complete randomized block design with a 2 × 2 × 2 factorial arrangement of treatments. The significance of treatments w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
(69 reference statements)
0
2
0
Order By: Relevance
“…Monensin modulates the rumen microbiome, leading to more propionate production and providing more energy to the animal since propionate increases hepatic gluconeogenesis (Ipharraguerre and Clark 2003) and reduces the ketone body (Scharen et al 2017) in blood circulation, indicating a reduction in lipolysis (Agustinho et al 2021) The increase in ruminal propionate could be accompanied by a reduction in the amount of methane produced in the rumen and an increase in blood glucose concentration (Nagaraja et al 1997). This study confirmed that monensin reduces BHB concentration in blood serum.…”
Section: Discussionmentioning
confidence: 99%
“…Monensin modulates the rumen microbiome, leading to more propionate production and providing more energy to the animal since propionate increases hepatic gluconeogenesis (Ipharraguerre and Clark 2003) and reduces the ketone body (Scharen et al 2017) in blood circulation, indicating a reduction in lipolysis (Agustinho et al 2021) The increase in ruminal propionate could be accompanied by a reduction in the amount of methane produced in the rumen and an increase in blood glucose concentration (Nagaraja et al 1997). This study confirmed that monensin reduces BHB concentration in blood serum.…”
Section: Discussionmentioning
confidence: 99%
“…In the field of bovine veterinary medicine, the pivotal role of mineral deficiencies in modulating the immune system should not be underestimated. Recent investigations have elucidated that the provision of micronutrient supplements has demonstrably reduced the count of milk somatic cells (SCC), bolstered immune function, and elicited anti-inflammatory and antioxidant responses in dairy cattle during the periparturient period ( 69 , 70 ). Extensive research has shown that these deficiencies can lead to immunosuppression, making the animals more susceptible to infectious diseases such as mastitis ( 42 ).…”
Section: Trace Minerals Role In Bovine Mastitis Prevention During Per...mentioning
confidence: 99%
“…Therefore, these two drugs were selected to stimulate cells to induce microenvironmental changes. [28][29][30] In this experiment, probe-incubated bare cells served as a control group. For the experimental group, two groups of cells were first incubated with monensin and nystatin for 1 h, and then the VisP was added to continue to incubate the cells for imaging with the same parameters.…”
Section: Imaging Intracellular Viscosity Under Inflammatory Statementioning
confidence: 99%